Dynamics in pre-service teachers’ beliefs about multilingualism and linguistic diversity in education: a Q methodology intervention study - Denis Weger (Cogent Education, 2025)
This study addresses the structural challenges multilingual students face in predominantly monolingual school systems and the role of teachers in integrating students’ full linguistic repertoires. Promoting such inclusive practices requires specific professional beliefs, which have increasingly come into focus in teacher education research in recent years. Traditional methods like Likert-based surveys are prone to socially desirable responses and often fail to capture the interconnected nature of beliefs. To address these limitations, this study applies Q methodology–an approach combining qualitative and quantitative elements–in a pre/post design to offer a more nuanced view of belief structures and their development. Thirty pre-service teachers participated in a course on multilingualism and sorted 30 statements in a forced-choice distribution. The analysis revealed a shift from predominantly positive to uniformly positive beliefs. Monolingual perspectives present in the pre-test disappeared post-course, replaced by more inclusive views that occasionally included seemingly contradictory elements, nuances often overlooked by conventional methods. The findings highlight Q methodology’s potential to uncover the complexity of teacher beliefs while reducing response bias. They also underscore the value of teacher education programs that explicitly address multilingualism and the role of the language of schooling in fostering more inclusive beliefs among future teachers.